THE EFFECT OF ANIMATION MEDIA ON SMOKING HARM KNOWLEDGE WITH PREGNANCY AMONG PREGNANT WOMAN AT BHUMIBOL ADULYADEJ HOSPITAL - Thongpaknum, Chayaphat (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This quasi-experimental research aimed to study the effect of animation media on smoking harms knowledge with pregnancy among pregnant women at Bhumibol Adulyadej Hospital using Edgar dale's conceptual framework, cone of experience theory (Dale, 1996). The samples were 48 pregnant women receiving antenatal care for the first time at the antenatal care unit at Bhumibol Adulyadej Hospital. They were purposively selected and divided, 24 for the experimental and 24 for the control groups. The experimental group received the animation media on smoking harm knowledge, while the control group received knowledge from the electronic brochures. The research instruments consisted of the animation media on smoking harm knowledge with pregnancy and the animation media on the smoking harm knowledge scale. The content validity index (CVI) was obtained from three-panel experts, equaling .90. The reliability was determined using the KR-20 equal to .70. Research data were analyzed using descriptive statistics and a t-test. The results showed that the experimental and control groups had a score on smoking harm knowledge with pregnancy significantly higher than before participating in the program at a .05 level. Furthermore, the experimental group had a significantly higher mean score on smoking harm knowledge with pregnancy than the control group (t = 1.14, p = .003). It is recommended that nurses can use this animation media on smoking harm knowledge with pregnancy to provide health education among pregnant women in the antenatal care unit. Thus, they can improve their understanding of cigarette smoking harms and take proper care of themselves and their fetuses during pregnancy.